Thermoeconomic analysis of wheat flour agroindustrial plant (2015)
This paper presents the development of an exergy and thermoeconomic analysis of a wheat flour agro-industrial plant, which was aimed to evaluate the energy use and establish the operation cost of its components, and to understand the cost formation process and the cost flow. It was found that throughout the production process exists an exergy destruction ratio of 95,08 %. It identified improvement opportunities in relation to cost, has recommended alterations with regard matter flows or an economic investment for change some components with low exergoeconomic factors: 2% planer of wheat bran, 3% knurled roller grinding benches and 5% smooth roller grinding benches. Copyright © 2015 by ASME.